The statistical invisibility of black, afro-colombian and palenque-rooted populations in colombia (2010)
One of the more obvious forms of structural racism towards Afro-Colombian, black and Palenque-rooted populations in Colombia is the lack of statistical information specific to account for their existence, their characteristics and peculiarities. As such data are relevant to ensure, for example, the formulation of public policies and the recognition of historical rights violated in this population, the Afro-Colombian Social Movement, academic groups and organizations interested in raising their profile have generated dialogue and consultation processes with the State agencies responsible for official statistics. This is to achieve genuine inclusion not only in the census process, but in the national statistical system.